PENINGKATAN KETERAMPILAN MENULIS ARGUMENTASI MELALUI MODEL THINK PAIR SHARE DAN MEDIA AUDIOVISUAL PADA SISWA KELAS X-10 SMA NEGERI KEBAKKRAMAT - Fitria Cahyaningrum; Andayani Andayani; Kundharu Saddhono (Jurnal Pendidikan dan Kebudayaan, 2018)
This research aims to improve learning process quality of writing argumentation text and argumentation writing skills through the Think Pair Share model with audiovisual media of students X-10 grade SMA Negeri Kebakkramat. This research was a Classroom Action Research (CAR) with two cycles. Data sources include events, informants, and documents. Data collection through interviews, observation, and document analysis. Data validity by triangulation method technique, triangulation of data source and informant review. Data analysis technique using comparative descriptive analysis technique. Think Pair Share model with audiovisual is able to improve the quality of learning process of argumentation writing skill indicated by teacher and student performance. In pre-cycles, the teacher and student performance values were still below the achievement indicator. In cycle I, the value of teacher performance increased to 69.29 and the percentage of student performance of 47.22%. Meanwhile, in cycle II the teacher performance value became 80.71 and the percentage of student performance became 78.95%. After the action done on the first cycle, there were only 21 students who achieved the value of KKM (minimum completeness criteria) which means it did not meet the achievement indicators. Implementation of Think Pair Share with audiovisual media in cycle II showed a significant improvement in argumentation writing skill, that is, score of 31 students exceeded KKM. In conclusion, the application of Think Pair Share model with audiovisual media is able to improve learning process quality and argumentation writing skill for the tenth grade students of SMA Negeri Kebakkramat.Â